2020
DOI: 10.21203/rs.2.20471/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictive factors for myocardial infarction in pre-hospital emergency care

Abstract: Background: Identifying predictive factors based on procedures carried out by emergency medical teams may speed up the diagnosis of AMI. By shortening the time between the onset of the pain and the initiation of coronary reperfusion, patient prognosis can be improved Methods: The study was conducted on residents of the Bielsko-Biała district, served by state ambulance service Medical Response Teams (MRT). The patients were assigned to the following groups: Group A (n = 338) - patients with chest pain in whom i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
1
2
0
3
Order By: Relevance
“…Furthermore, Ilczak, et al,(2021) (31) conducted a study to evaluate the predictors of stress that paramedics, nurses These results were in agreement with a study conducted to examine occupational stress for two hundred and forty four psychiatric nurses in China. The study showed high stress level in male nurses than females that was due to physical violence and verbal assault from patients to male nurses (34) .…”
Section: Resultssupporting
confidence: 65%
“…Furthermore, Ilczak, et al,(2021) (31) conducted a study to evaluate the predictors of stress that paramedics, nurses These results were in agreement with a study conducted to examine occupational stress for two hundred and forty four psychiatric nurses in China. The study showed high stress level in male nurses than females that was due to physical violence and verbal assault from patients to male nurses (34) .…”
Section: Resultssupporting
confidence: 65%
“…[20][21][22][23][24] Dentre os aspectos mentais, o estresse se revelou como a repercussão mais frequente nos estudos selecionados. [14][15][16]19 Nesse aspecto, os níveis mais elevados desse estado emocional foram encontrados na população do sexo feminino [14][15][16] , em enfermeiros [15][16] e paramédicos. 14 Os principais preditores apontados nas pesquisas para elevação do nível de estresse durante a pandemia da COVID-19 foram o medo de contrair a doença, a diminuição do nível de segurança durante a realização de procedimentos 15 , o aumento da carga horária e a redução da capacidade de adaptação.…”
Section: Discussionunclassified
“…[14][15][16]19 Nesse aspecto, os níveis mais elevados desse estado emocional foram encontrados na população do sexo feminino [14][15][16] , em enfermeiros [15][16] e paramédicos. 14 Os principais preditores apontados nas pesquisas para elevação do nível de estresse durante a pandemia da COVID-19 foram o medo de contrair a doença, a diminuição do nível de segurança durante a realização de procedimentos 15 , o aumento da carga horária e a redução da capacidade de adaptação. 16 Os níveis elevados dessa reação ocasionaram o sentimento de fadiga emocional e insegurança no local de trabalho 15 e poderiam levar à diminuição na qualidade assistencial dos serviços de saúde.…”
Section: Discussionunclassified
“…Based on the research of A. Putot, the onset of symptoms of a heart attack along with acute infection is characterized by symptoms of tachycardia (>100 beats/min), tachypnea (>24 breaths/min), and symptoms of fever (>39ᵒC) [9]. According to research by T. Ilczak, the parameters considered significant as predictors of a heart attack include respiratory rate less than 12/minute and heart rate less than 60/minute [10].…”
Section: Introductionmentioning
confidence: 99%